2010
DOI: 10.1002/jbmr.312
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia induces resistance to PTH bone anabolism in mice via oxidized lipids

Abstract: In hyperlipidemia, oxidized lipids accumulate in vascular tissues and trigger atherosclerosis. Such lipids also deposit in bone tissues, where they may promote osteoporosis. We found previously that oxidized lipids attenuate osteogenesis and that parathyroid hormone (PTH) bone anabolism is blunted in hyperlipidemic mice, suggesting that osteoporotic patients with hyperlipidemia may develop resistance to PTH therapy. To determine if oxidized lipids account for this PTH resistance, we blocked lipid oxidation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 42 publications
4
79
0
Order By: Relevance
“…Consistent with the evidence for a linkage between atherosclerosis and osteoporosis in humans, ApoE-null (ApoE-KO) mice or LDL receptor-null mice fed a HFD exhibit reduced bone mass (24,48,49,53). The mass and structural integrity of the skeleton are maintained by teams of osteoclasts and osteoblasts that, respectively, resorb old bone and replace it with new (38).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Consistent with the evidence for a linkage between atherosclerosis and osteoporosis in humans, ApoE-null (ApoE-KO) mice or LDL receptor-null mice fed a HFD exhibit reduced bone mass (24,48,49,53). The mass and structural integrity of the skeleton are maintained by teams of osteoclasts and osteoblasts that, respectively, resorb old bone and replace it with new (38).…”
mentioning
confidence: 73%
“…ports in both ApoE-KO and LDL receptor-null mice (24,48,49,53). However, in the earlier studies, the HFD was begun at ϳ1 to ϳ3 mo of age, when growth and bone formation are high (18).…”
Section: Discussionmentioning
confidence: 99%
“…The ApoA-I mimetic peptide, D-4F, reduced serum markers of bone resorption in mice (39). Decreased bone mineral density was noted in subjects carrying familial defective ApoB-100 (40).…”
Section: Discussionmentioning
confidence: 96%
“…They were also found to affect bone resorption by increasing osteoclastogenesis cytokines production such as receptor activator of nuclear factor-κB (RANKL) and interleukin-6 from both T-lymphocytes and osteoblasts [17][18][19][20][21]. Furthermore, it has been reported that oxidized lipids down regulate parathyroid hormone receptor (PTH1R) in osteoblasts causing resistance to PTH [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%